(untitled) (TEST BioLaw Journal - Rivista di BioDiritto, 2021)
This essay deals with the right to health in the perspective of access to pharmaceuticals. The availability of safe and accessible medicines, especially in the last two decades, has often been lacking even in the “Global North”. The Covid-19 pandemic and the challenge of vaccines distribution represents a further “market failure” of the current regulatory asset. It is therefore urgent to reform the EU legislation providing incentives in the biomedical field, now centered on the grant of exclusive rights. Some proposals appear adequate to restore an appropriate balance between the various interests that revolve around health protection. A public European biomedical research infrastructure, a “CERN of medicines”, appears the most meaningful and timely suggestion.